Предмет: Алгебра,
автор: 123456547235342
Даю 15 баллов
Доведіть тотожність:(х-2)*(х-1)*х(х+1)+1=(х^2-х-1)^2
Ответы
Автор ответа:
0
(х-2)*(х-1)*х(х+1)+1=(х^2-х-1)^2
(х^2-2х-х+2)*(х^2+х)+1=(х^2-х-1)^2
х^4-2х^3-х^3+2х^2+х^3-2х^2-х^2+2х+1=х^4-х^2+2х+1
х^4-х^2+2х+1= х^4-х^2+2х+1
(х^2-2х-х+2)*(х^2+х)+1=(х^2-х-1)^2
х^4-2х^3-х^3+2х^2+х^3-2х^2-х^2+2х+1=х^4-х^2+2х+1
х^4-х^2+2х+1= х^4-х^2+2х+1
Похожие вопросы
Предмет: Физика,
автор: ttffttf99
Предмет: Українська мова,
автор: Аноним
Предмет: Математика,
автор: odhhvfn
Предмет: Математика,
автор: школаия
Предмет: История,
автор: LiliMilki